Strengthening Legal Certainty in the Implementation of Metrological Supervision and Guidance - Mochamad Ali Fajar; Diyan Isnaeni; Moh. Muhibbin (JURNAL USM LAW REVIEW, 2025)
Legal metrology plays a crucial role in safeguarding consumer rights, ensuring fair trade, and enhancing state credibility through accurate measurements and standardized verification systems. However, in Indonesia, the existing regulatory framework, primarily based on Law No. 2 of 1981, has become increasingly obsolete amidst digital transformation, administrative decentralization, and evolving public governance norms. This article critically analyzes the structural and normative fragmentation in Indonesia’s legal metrology system, focusing on regulatory inconsistencies, procedural ambiguity, and institutional disconnect between national and regional metrology units (UMLs). Using a normative juridical method and a comparative approach, this study identifies gaps in legal certainty (rechtszekerheid), especially regarding digital verification, public outreach, and inspector professionalism. Drawing insights from international best practices and recent jurisprudence, the article proposes a comprehensive legal reform agenda, including statutory revision, codification of digital authority, institutional restructuring, and participatory governance mechanisms. The novelty of this research lies in its integration of legal metrology within broader administrative law and digital governance discourses, positioning it not merely as a technical domain but as a pillar of regulatory justice. As a strategic recommendation, the Government of Indonesia must immediately initiate legislative reform to replace Law No. 2 of 1981 with a modern, harmonized statute that codifies digital standards, aligns with decentralization mandates, and guarantees procedural protection for both consumers and regulated entities.